Capacity Development Of The Village Security And Development Committee Of Kampung Batu 37 Darat, Selangor - Hasbollah, Hasif Rafidee (2006)

(untitled)
This study attempts to illustrate the importance of capacity development in the Village Security and Development Committee (VSDC) of Kampung Batu 37 Darat, Sabak Bernam, Selangor. The objectives of the study are firstly, to determine the organisation capacities that contribute to the capacity development of the VSDC; secondly, to determine the styles of leadership that contribute to the capacity development; thirdly to determine the elements of community development that contribute to the capacity development; and finally to determine the level of capacity development of the VSDC. A total of 82 respondents were selected, whereby all 16 respondents were among the VSDC committee members and 66 respondents were among the villagers chosen via stratified random and convenient sampling. The data were collected using the quantitative method. The SPSS software was used to analyse the descriptive statistics and cross tabulation. The findings of the study showed that the variables used for organisation capacities like partnership, resources and technical expertise, styles of leadership, which include autocratic and democratic, and elements of community development like attitude, skills and knowledge contributed to the capacity development of the VSDC. The study also revealed that the levels of capacity development of the VSDC were at a high level in the planning, decision-making and implementation activities. Therefore, this study evidently showed that there was capacity development among the VSDC of the village.